ANALISIS HADIST TARBAWY TENTANG MATERI PEMBELAJARAN AGAMA ISLAM (KAJIAN HADIST KONTEMPORER) - Nurul Hidayah; Khusnul Khotimah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2021)
Islamic learning materials are important as stimulation to students. Knowledge of the teachings has been systematically discussed in islamic sciences, each of which emphasizes certain aspects of the teaching. Islamic learning materials are very basic and important for the development of learners, because in fact educators not only transfer knowledge, but also the heirs of culture and values so as to make human character in accordance with the Qur'an and As-Sunnah. In this case, this study aims to explain the islamic material contained in the Hadith Tarbawy. This study uses descriptive qualitative research that explores as deeply as possible islamic learning materials from the study of Hadith Tarbawy, this type of research is a research library (library research). This research, collection techniques are done using documentation methods, namely by searching for data or information from books, books and other records. It is then analyzed using miles and hybermen models. The results of this study explain: (1). Aqidah material is a material that explains, that the place of asking and complaining only to Allah swt. (2). The material of the Qur'an is a material that explains, about the study of reading the Qur'an and tajwid, the nature and makhrajnya ma'na and its interpretation. (3). Fiqh material is a material that explains the rules of Islam and knows halal and haraam, the laws concerning worship and muamalah. So it can be concluded that the three materials can not be separated, because in fact matri Aqidah, Qur'an, Fiqh is very important in terms of daily life.